Model Pengelolaan Agroforestri Kakao (Theobroma Cacao L.) terhadap Kontribusi Pendapatan Rumah Tangga (Suatu Kasus di Kecamatan Anyar Kabupaten Serang Provinsi Banten) - Sri Wahyuningsih; Andjar Astuti (Jurnal Agribisnis Indonesia, 2015)
The research aims to analyze the management of cocoa agroforestry, labor allocation and household income of farmers in cocoa agroforestry management activities as well as the contribution of agroforestry to household income of cocoa farmers in the Anyar District Serang Regency Banten Province. The method used in this research is a survey using two stage cluster sampling method. Samples taken are as many as 60 farmer of 400 populations scattered from cocoa agroforestry farmers in the Anyar District Serang Regency Banten Province. The results showed that the management of cocoa agroforestry in the Anyar District during year 1 to year 7 consists of 5 stages, namely : land clearing, planting, maintenance, harvesting and post-harvest. Average allocation of labor in the cocoa agroforestry management activities in the Anyar District is at 440,18 HOK/Ha/Year with the following composition : 1,21 HOK/Ha/Year in the planting stage, 132,5 HOK/Ha/Year in the maintenance stage, 145,22 HOK/Ha/Year in the harvesting stage and 161,25 HOK/Ha/year in the post-harvest stage. Average household income of cocoa agroforestry farmers in the Anyar District is Rp. 84.451.377/Year which includes income from cocoa agroforestry is Rp. 26.880.210/Year by contributing to the household income of farmers by 31,83%/Year and income from non-cocoa agroforestry is Rp. 57.571.167/Year by contributing to the household income of farmers by 68,17%/Year.